Myth of the hanging tree: stories of crime and punishment in territorial New Mexico - Tórrez, Robert J. (University of New Mexico Press, 2008)
Myth of the hanging tree -- Legal hangings and capital punishment in New Mexico -- Two of history's forgotten desperados -- Murder, politics, and justice in frontier New Mexico : the framing of Perfecto Padilla -- The man who was hanged twice -- Witness to a hanging -- Shoot-out at Gallegos Canyon -- Judicial gems : the art of judicial sentences in territorial New Mexico -- "Young, ignorant, and immoral" : murder by poison at Hillsboro, New Mexico -- Paula Angel : a search for the "only woman ever hanged in New Mexico" -- The old penitentiary : New Mexico's "first new public building"